Arnold Geulincx Ethics With Samuel Beckett's Notes - van Ruler, Han; Uhlmann, Anthony; Wilson, Martin A. (Brill, 2006)
Arnold Geulincx (1624-1669) is a key figure in the history of ideas, whose concepts have been seen as precursors to those developed by Spinoza, Malebranche, Leibniz and Kant. His Ethics presents a treatment of virtue from the standpoint of occasionalist metaphysics. The great Irish writer Samuel Beckett stated that Geulincx, with his emphasis on the powerlessness and ignorance of the human condition, was a key influence on his works. This is the first complete version of the text to appear in a modern language. It includes the full text of the Ethics and Beckett's notes to his reading of Geulincx. Shedding new light on important moments of intellectual history, it is a major event for students of philosophy and literature.